Impact : impress your way to success - Vickers, Amanda (Prentice Hall Life, 2012)
Learn how to harness the power of personal impact so you can earn more, live more and be more. Impact is everything. It gives us huge competitive advantages as we impress others and are remembered when it matters the most. It gives us the confidence to succeed and achieve our personal and professional goals and enables us persuade and influence others so we can get what we want, when we want. This book will show anybody how to use the power of impact to make a great first impression; raise their profile; secure that promotion; land their dream job; be the person everyone remembers; make amazing presentations and impress everyone they meet in any situation. Covering topics such as confidence and positive thinking, this book is relevant to everyone from graduates, to top managers and everyone else in between.